Evaluation of the Effectiveness of Peer Assisted Learning in Forensic Medicine & Toxicology for Third Phase MBBS Students (Indian Journal of Forensic Medicine & Toxicology, 2025)
ABSTRACT Background: With the introduction of Competency-Based Medical Education (CBME) by the National Medical Commission (NMC) in India, teaching methodologies that foster competencies like leadership, team building, and independent learning are essential. Peer-Assisted Learning (PAL), where peers help each other learn, is one such methodology.Aim and objective: This study aimed to evaluate the effectiveness of PAL in enhancing the understanding of subjects and overall learning experience of undergraduate students. The objective was to compare the test scores of students taught by PAL with those taught by didactic lectures. Materials and method: This comparative analytical study involved 100 third-phase part 1 MBBS students at Hind Institute of Medical Sciences, Barabanki, U.P., India, from October to December 2023. Fifty students each were assigned to Group A (didactic lectures) and Group P (PAL) using consecutive sampling. Student performance was assessed using paired t-tests within each group, and the efficacy of PAL was evaluated by comparing post-test scores using unpaired t-tests. Feedback was collected via a Google form to analyze learners' attitudes and views.Results: There was consistent improvement in the post test scores of Group P; also there is significant improvement in the performance in test-3(p< .0006). Majority of students found the sessions engaging and found them helpful.Conclusion: PAL has shown positive impact on students learning outcome. It also promotes independent learning and team building in students. However, the results are influenced by factors such as phase of student, planning involved and quality of lesson plan.
Keywords: Peer Assisted Learning, Comparitive study, Forensic Medicine and Toxicology, Undergraduate students, Innovation in Medical Education